PENERAPAN STRATEGI MODELLING THE WAY UNTUK MENINGKATKAN KEMAMPUAN SHALAT WAJIB SISWA - ASNGADI ASNGADI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This research aims to improve the ability to perform mandatory prayers through modeling the way strategies in students of grade IV SDN Tri Mulya Agung Semester even the 2018/2019 school year with the number of students 23 students. The methods used in this study are class-action research methods, data collection through observation, interviews and tests or assignments, while data analysis is done with interactive models. While the activity is carried out in interactive form with the process of collecting data as a cyclical process. The results showed that through modeling strategies the way can improve the ability to perform mandatory prayers in students of grade IV SDN Tri Mulya Agung Semester even the year of study 2018/2019. Learning activities from cycle I to cycle II there is an increase: aspects of reading the pillars of prayer (average value increases 1.1; percentages rise 21.8%; from good category to very good), aspect of reading prayer conditions (average value up 0.7; percentage up 14.8%; from good category to very good); aspects of reading things that cancel prayers (average value increased 0.7; percentage rose 15.7%; from good category to very good), and aspect of prayer practice (average value rose 0.9; percentage rose 18.3%; from good category to very good). Student learning outcomes from the initial condition to cycle II increased, from 7 students (30%) who got completed grades to 23 students (100%). There was an increase of 16 students (70%) and the grade point average from 60.2 to 85.0, an increase of 24.8. ABSTRAKPenelitian ini bertujuan mendeskripsikan untuk meningkatkan kemampuan melakukan sholat wajib melalui strategi modelling the way pada siswa kelas IV SDN Tri Mulya Agung Semester genap tahun pelajaran 2018/2019 dengan jumlah siswa 23 siswa. Metode yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas, pengumpulan data melalui observasi, wawancara dan tes atau penugasan, sedangkan analisis data dilakukan dengan model interaktif. Sedangkan aktifitas dilakukan dalam bentuk interaktif dengan proses pengumpulan data sebagai proses siklus. Hasil penelitian menunjukkan bahwa melalui strategi modelling the way dapat meningkatkan kemampuan melakukan sholat wajib pada siswa kelas IV SDN Tri Mulya Agung Semester genap tahun pelajaran 2018/2019. Aktivitas belajar dari siklus I ke siklus II terdapat peningkatan: aspek membaca rukun sholat (nilai rata-rata meningkat 1,1; persentase naik 21,8%; dari kategori baik menjadi amat baik), aspek membaca syarat sholat (nilai rata-rata naik 0,7; prosentase naik 14,8%; dari kategori baik menjadi amat baik); aspek membaca hal yang membatalkan sholat (nilai rata-rata meningkat 0,7; persentase naik 15,7%; dari kategori baik menjadi amat baik), dan aspek praktek sholat (nilai rata-rata naik 0,9; prosentase naik 18,3%; dari kategori baik menjadi amat baik). Hasil belajar siswa dari kondisi awal ke siklus II mengalami peningkatan, yaitu dari 7 siswa (30%) yang mendapat nilai tuntas menjadi 23 siswa (100%). Terjadi peningkatan sebanyak 16 siswa (70%) dan nilai rata-rata kelas dari 60,2 menjadi 85,0, meningkat sebesar 24,8.